The Implementation of Diagnostik Assessment in Geography Education Within the Merdeka Curriculum - Arinto, Fendya Jauhari Budi; Ginting, Rosalina Br; Wuryandini, Endang (Cetta: Jurnal Ilmu Pendidikan, 2025)
This study explores the implementation of diagnostic assessment in Geography education within the Merdeka Curriculum framework at SMA Negeri 1 Blora. Diagnostic assessment serves to identify students' prior knowledge, enabling teachers to tailor instruction and design personalized strategies aligned with curriculum goals. Employing a descriptive qualitative case study approach, data were collected through interviews with teachers and students, classroom observations, and document analysis. Findings reveal that diagnostic assessment is conducted in three stages planning, implementation, and follow-up. During planning, teachers prepare assessment tools aligned with curriculum objectives. Implementation occurs before new topics to gauge students' baseline knowledge, while follow-up involves adjusting teaching methods based on assessment results to address learning gaps. Challenges include limited time and difficulty in developing comprehensive, accurate questions. Despite these, diagnostic assessment enhances students’ Geography understanding and improves education quality under the Merdeka Curriculum. The study emphasizes its role in fostering a student-centered learning environment.